KEMAMPUAN BERPIDATO MAHASISWA UNIVERSITAS KATOLIK MUSI CHARITAS - Tresiana Sari Diah Utami (Universitas Katolik Musi Charitas, 2023)
Speaking skills in Indonesian is a language skill that needs to be mastered well. This is because speaking skills are one of the most important indicators for student success in learning languages. Speech is one of the skills that must be mastered by students. The research focuses on the ability to make speeches seen from the structure of the speech. the structure of the speech, among others, opening, content, and closing. This study aims to describe the speech skills of Musi Charitas Catholic University students, seen from the structure of the building. The method used in this research is descriptive qualitative. The data source is from tests conducted on students of Musi Charitas Catholic University batch 2021, totaling 84 students. The results of tests conducted on research subjects were then transcribed and became a source of data. The research instrument is a student's speech test by referring to the instruments that have been used previously. The results showed that 88.8% of the research subjects were able to produce the opening part, 80.4% of the research subjects were able to produce the content part, and 71.3% of the research subjects were able to produce the closing part.